Assessment of changes in the phenotype, intensity of degranulation, death and lysis of neutrophils in ex vivo modeling of Staphylococcal bacteremia - Aleksandr L. Kravtsov; Svetlana A. Bugorkova; Svetlana N. Klyueva; Tatyana P. Shmelkova; Vitaly A. Kozhevnikov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2023)
Introduction. At present, it is important to study the interaction of Staphylococcus aureus with human innate immunity cells under conditions of ex vivo bacteremia modeling, but not only in experiments with phagocytes previously isolated from the blood.